معايير تحديد جودة الخدمة التعليمية وتقويم الأداء الجامعي في الجامعات السورية - ناصر, محمد جودت; طرابلسية, شيراز محمد عشير (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تتمحور هذه الدراسة حول تحديد جودة الخدمة التعليمية المقدمة في مؤسسات التعليم العالي السورية، وذلك بالتطرق لبعض المعايير المهنية المستخدمة في تقييم أداء المؤسسات التعليمية استناداً لمتطلبات منظمات وهيئات الاعتماد. مشيرة إلى أنجع الأساليب الممكنة لتطوير أداء الجامعات كمؤسسات تربوية تعليمية رائدة ومنظومات ديناميكية فاعلة في خلق الكادر القادر على مواكبة احتياجات المجتمع ومتطلبات العولمة. ومتوصلة الى مجموعة من النتائج مفادها: عدم استخدام مؤسسات التعليم العالي السورية لمعايير الجودة العالمية نتج عنه انخفاض في جودة الخدمة التعليمية المقدمة من قبلها. وُتختتم الدراسة بمجموعة من التوصيات كان من أهمها اقتراح بعض معايير تقويم الأداء الجامعي في إطار المجالات التي تمت دراستها مع ضرورة التفكير بإيجاد آلية مناسبة لتطبيق هذه المعايير في الواقع العملي بما يتوافق مع رؤى ورسالة هذه الجامعات وينسجم مع استراتيجية التعليم فيها، الأمر الذي ينعكس بكل تأكيد على جودة الخدمة التعليمية المقدمة وإمكانية ضبطها وتحسينها بشكل دائم. The present study focuses on identifying the quality of educational service provided in Syrian higher education institutions in relation to some professional standards used in evaluating the performance of educational institutions fulfilling the requirements of the academic accreditation agencies. Pointing to the most appropriate practices for improving the performance of universities to become pioneer educational institutions and active dynamic organizations contributing to human resource development, the study reaches various results leading to the conclusion that Syrian higher education institutions provide poor quality of educational and research services due to their nonconformity to international standards. The study concludes with some recommendations, the most important of which is the suggestion of some standards for evaluating the university performance in the context of studied areas, together with the necessity of finding the appropriate mechanism for the application of those standards on the ground taking into consideration the vision, mission and strategy of the university. This will certainly be reflected on the quality of educational service and the possibility of controlling and improving it continually.